Parents of Disability-Teenage Communication Forming Positive Attitudes about Sexuality - Putri Santy; Yulia Fitri (Science Midwifery, 2022)
Parents with disabilities lack knowledge about reproductive health. Low knowledge affects the provision of information to adolescents. Unopen communication between parents and adolescents can give rise to a child's negative attitude toward sexuality. This study aims to determine the relationship between parents with blind disabilities and adolescents' attitudes toward premarital sexual relations. The cross-sectional study included 83 adolescents aged 14-19 from parents with disabilities in the Banda Aceh City area. The technique of sampling the total population according to the criteria of inclusion and exclusion. The results showed a meaningful relationship between communication between parents with disabilities-adolescents and attitudes about premarital sexual relations (ρ=0.000). Parent-to-adolescent communication plays a role in shaping positive attitudes in adolescents about premarital sexual intercourse. It is hoped that parents with visual impairments will increase their knowledge about sexuality and explain what is known to adolescents openly.